2018
DOI: 10.1111/cen.13572
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights on testicular volume and testosterone replacement therapy in Klinefelter patients undergoing testicular sperm extraction. A retrospective clinical study

Abstract: Age at TESE, anthropometric measures, testis volume, sex hormones levels and semen parameters are not predictive parameters of SRR. Among TRT patients, reduced gonadotropin is related to failure in sperm retrieval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
21
0
1
Order By: Relevance
“…Madgar et al, 36 for example, showed that testicular volume was significantly higher in men with positive SRR. However, there are several studies reporting that testicular atrophy does not affect the success of SR. 9,[27][28][29]32,37 Garolla et al, 28 indeed, observed a 23% SRR even in KS patients with testicles < 1 mL. Our results support these findings as we failed to find any relationship between testicular volume and SRR in NOA patients with KS.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Madgar et al, 36 for example, showed that testicular volume was significantly higher in men with positive SRR. However, there are several studies reporting that testicular atrophy does not affect the success of SR. 9,[27][28][29]32,37 Garolla et al, 28 indeed, observed a 23% SRR even in KS patients with testicles < 1 mL. Our results support these findings as we failed to find any relationship between testicular volume and SRR in NOA patients with KS.…”
Section: Discussionsupporting
confidence: 87%
“…9 So far, there is a lack of reliable clinical and biological predictors for sperm retrieval success in NOA patients with KS. [27][28][29] Advanced paternal age has been considered a negative predictive factor for SR in Klinefelter men undergoing TESE. 30,31 Ozer at al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, although the endocrine feedback regulation is definitely disturbed, impaired T production cannot be the reason for the lowered peripheral serum T levels. Testes of KS patients are phenotypically described as small and firm with volume of approximately 2-2.5 mL vs. the healthy normal range above 12 mL per testis 19,20 which is due to a dramatically altered testicular architecture caused by germ cell loss and Leydig cell hyperplasia. We reported previously that the vascularization of testes in 30 weeks old mice was altered mainly due to a changed blood vessel composition 18 .…”
mentioning
confidence: 99%